Measurements of proton high-order cumulants in √sNN=3 GeV Au+Au collisions and implications for the QCD critical point - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review letters, 2022)
We report cumulants of the proton multiplicity distribution from dedicated fixed-target Au+Au collisions at √sNN=3.0  GeV, measured by the STAR experiment in the kinematic acceptance of rapidity (y) and transverse momentum (pT) within −0.5<y<0 and 0.4<pT<2.0  GeV/c. In the most central 0%–5% collisions, a proton cumulant ratio is measured to be C4/C2=−0.85±0.09 (stat)±0.82 (syst), which is 2σ below the Poisson baseline with respect to both the statistical and systematic uncertainties. The hadronic transport UrQMD model reproduces our C4/C2 in the measured acceptance. Compared to higher energy results and the transport model calculations, the suppression in C4/C2 is consistent with fluctuations driven by baryon number conservation and indicates an energy regime dominated by hadronic interactions. These data imply that the QCD critical region, if created in heavy-ion collisions, could only exist at energies higher than 3 GeV.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 21.07.2022